Metasurface collectors for ambient RF energy harvesting applications - Ahmed Ghaleb Amer, Abdulrahman (2022)
Metasurface is a planar type of metamaterial that is preferred in all electromagnetic applications due to its simplicity. Metasurfaces can be constructed using an array of electrically small resonators. This work investigates the feasibility of using small, highly efficient metasurface structures as RF collectors for energy harvesting applications. The first part of this work discussed a new metasurface split-ring resonator (SRR) absorber as an energy harvester. An array of 7x7 SRR metasurface resonators were designed and fabricated to maximise energy absorption at broadband frequencies of 1.88 GHz to 6.4 GHz. An air layer is placed between the dielectric substrate and the ground plane to enhance the absorption bandwidth. In addition, four resistor loads placed on the splits of the top metallic layer of the resonator are used to achieve a polarization-insensitive, wide-angle from 0o up to 60o , higher absorption, and higher harvesting efficiency. The near-unity absorption of over 90% and the harvesting efficiency of around 88% are achieved over a wider frequency range. Therefore, an efficient miniaturized wideband metasurface energy harvester is introduced in the second part of this work. A design of the electromagnetic metasurface harvester inspired by an array of printed metallic electric ring resonators (ERR) is presented. A finite array of 5x5 ERR unit cells is analysed numerically and experimentally at 5 GHz band. The array is analysed for maximising radiation to AC conversion efficiency where a resistor terminates each resonator through a metallic via. The overall radiation to AC harvesting efficiency of about 91% and 78% was obtained numerically at normal incidence and different oblique incidence angles up to 60o , respectively. Unlike earlier metasurface harvesters that connected each resonator to a load, this novel design uses a feed network to connect all resonators to one load to increase the efficiency. The novel proposed metasurface is based on the doubleelliptical cylinder resonator that can capture energy at 5 GHz band. The simulation results yielded radiation to AC efficiency of 94% at normal incidence. A finite array of 4x4 unit cells was fabricated and tested experimentally for verification.